Performance Evaluation of Code Division Multiple Access (CDMA) in terms of Power Measurement and Reduction - Syed Rizwan-ul- Hasan; Shakil Ahmed (Sir Syed University Research Journal of Engineering and Technology, 2011)
In this research paper the performance of the CDMA system has been analyzed with respect to PAPR (Peak to Average Power Ratio) measurement and its reduction. Simulation results verify that high peaks degrade the performance of CDMA, application of codes reduced high peaks and PAPR is a good measure for CDMA.